Determining the cost of apple production by applaying analitical calculation - Mamuza Milorad; Vaško Željko (Agroznanje, 2013)
Every agricultural producer is interested in the financial result of its production. For those producers who do not have regular and complete bookkeeping records, this result can be calculated using the analytical accounting calculations. This paper describes the determination of financial results and the cost of apple production on the example of one producer near Prijedor, on the basis of data on conditions and results of its apple production in 2009 on the area of 2 hectares. Calculating the actual costs and revenues was found that the producer on 2 hectares of plantations had a total annual cost of BAM 23.636, total revenues of BAM 45.200 and the profit of BAM 21.564. In addition to recognition if the profit is made and how much it is, every producer from the point of formation of the sales price and sales policy wants to know what is the cost price of his products. In the analyzed case, the cost production price was BAM 0.37 per kg of the first apple class and BAM 0.13 per kg of the second apple class.